Dari Benci Jadi Suka: Saat Kamu Mulai Mengenal Matematika - Bunga Puspita Sari; Kiran Firjayanti; Prihaten Maskhuliah (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2026)
Mathematics is a fundamental discipline that develops logical, critical, systematic, and creative thinking skills. However, many students perceive mathematics as difficult and intimidating, reducing their motivation and interest in learning. These perceptions often stem from ineffective teaching methods, limited conceptual understanding, negative learning experiences, and mathematics anxiety rather than the nature of mathematics itself. This study aims to explore the view that students do not inherently dislike mathematics but have not experienced meaningful and engaging learning approaches. The research employed a qualitative descriptive method using a library research approach. Data were collected from books, scientific journals, and educational articles and analyzed through content analysis. In addition, an online educational news article was examined to identify spelling and writing errors based on the Indonesian Spelling Guidelines (EYD Fifth Edition). The findings reveal that students' perceptions of mathematics are influenced by instructional methods, previous learning experiences, environmental support, and self-confidence. Contextual, interactive, and technology-assisted learning approaches can improve motivation and foster more positive attitudes toward mathematics. The language analysis also identified inaccuracies in capitalization, prepositions, punctuation, and loanword spelling in online news articles. These findings highlight the importance of collaboration among teachers, parents, schools, and the media in creating meaningful mathematics learning while promoting accurate Indonesian language use. Ultimately, students are expected to develop a more positive perception of mathematics by recognizing its relevance to daily life and experiencing engaging, enjoyable, and meaningful learning.